Terrestrial laser scanning in forestry: Accuracy and efficiency in measuring individual tree parameters - Zhangmai Li; Qinghua Qiao; Zibin Han; Xinyi Liu; Yueyang Wang; Hongzhao Tang; Lei Deng (PLoS ONE, 2025)
With the growing global emphasis on forest resource monitoring, evaluating the accuracy of retrieving key individual tree parameters-such as tree position, tree height, and diameter at breast height (DBH)-using Terrestrial Laser Scanning (TLS) has become an important research focus. TLS has been widely applied in forest surveys due to its significant advantages in data acquisition efficiency and measurement precision. However, studies on the accuracy of extracting forest parameters from single-station, single-scan TLS data remain limited, underscoring the need for systematic evaluation and validation. This paper analyzes the accuracy and effectiveness of TLS in extracting structural parameters (tree height and DBH) and its position using Poplar and Styphnolobium as examples by using TLS, Airborne laser Scanning (ALS), and combining with field measurements. Results show that tree height estimates from single-scan TLS is limited in accuracy: the RMSE of 11.61 m in the Populus plot and 2.13 m in the Styphnolobium plot. Within a 50 m radius, single-scan TLS achieves a tree detection rate of 55.96–64.26% and a DBH RMSE of 1.60 cm (RRMSE: 9.03%). In addition, the point root mean square error of individual tree measurements remains at 0.11 m. These findings highlight the potential of TLS as an effective tool for forest inventory and provide a basis for evaluating the reliability of TLS-based plot measurements.